Synthesis of silver nanoparticles in green binary solvent for degradation of 2,4-D herbicide: Optimization and kinetic studies - Nur Syahirah, Kamarudin; Rohayu, Jusoh; Aisyah, Abdul Jalil; Herma Dina, Setiabudi; Nuramira Fateha, Sukor (Elsevier Ltd, 2020)
In this study, well-dispersed and diminutive Ag nanoparticles have been successfully synthesized in binary solvent of Orthosiphon stamineus (OS) leaves extract and ionic liquids (ILs) via electrochemical method. ILs namely [BMIM Tf2N], [BMIM BF4] and [EMIM EtSO4] were used as solvent in the synthesis process to produce AgTf2N, AgBF4, and AgEtSO4. The characterization of Ag nanoparticles revealed that the particle size of the silver nanoparticles can be easily altered depending on the size of IL alkyl chain and anion, to produce ultrafine particles ranging from 8 to 25nm. Meanwhile, the photocatalytic activity of AgTf2N nanoparticles effectively degraded the highest amount of 2,4-dichlorophenoxyacetic acid (2,4-D) herbicide at 65.61%. The optimized model gave high removal percentage of 2,4-D at 97.80% (pH = 3.24; catalyst dosage = 0.009 g/L; 2,4-D concentration= 8.15mg L−1) with validation experiments of 1.28% error. Investigation of kinetic reaction showed the applicability of pseudo-first order kinetic to the process of 2,4-D degradation (R2 > 0.98) which positively predicted the constant elimination amount of 2,4-D throughout the photocatalytic process. Overall, the studies construed the crucial role of binary solvent in synthesizing and controlling the size of Ag nanoparticles for pollutant degradation.